A Educação Escolar Indígena No Estado De São Paulo: Uma Análise Sobre Aproximações E Distanciamentos Em Relação Às Diretrizes Nacionais - Silva, Rafael Afonso [UNIFESP] (2017)
The purpose of this research is to investigate public policies implemented and effected in the state of São Paulo for the education of indigenous peoples. Those policies are based on those developed on a national level after the promulgation of the Constitution in 1988 regarding the education of indigenous people, which established that indigenous education should be based on principles of differentiation and specificity, interculturality and bilingualism. This work attempts to establish how closely or remotely what is practiced in the state relates to what is established nationwide. The starting point of the work is a corpus of legal and normative documents, handled using the methodological approach of the policy cycle as described by Stephen J. Ball, which allows the identification and understanding of the different contexts that, according to the author, comprise the process of policy production from its conception to its implementation. Analysis of the documents show a continuous movement towards normatization as well as the establishment of directives that must be respected by the states during the implementation of the policies, always with the aim of guaranteeing the offer of an appropriate education in accordance to the specificities of the communities served. In the state of São Paulo, indigenous primary and secondary education only started to receive a specific management in 1997, with the creation of the Núcleo de Educação Indígena (Center for Indigenous Education). However, in 2003, after a public audience by the Ministério Publico Federal (National Public Ministry – the body of public prosecutors) to check the state of primary and secondary indigenous education in the state, Terms of Adjustment of Conduct were instituted between the Ministry of Education (MEC), the Department of Education of the State of São Paulo (Secretaria Estadual de Educação de São Paulo), the Department of Education of the Municipality of São Paulo (Secretaria Municipal de Educação de São Paulo) and the National Indian Foundation (FUNAI) which defined joint obligations necessary to guarantee that primary and secondary indigenous education in the state fulfilled constitutional precepts and was aligned with nationwide policies. Thereafter there is a rapid shift in policies in the state, with the creation of dozens of indigenous schools, the establishment of a course of higher education for the intercultural training of indigenous professors as well as the creation of a Statewide Policy of Attention to Indigenous Peoples (Política Estadual de Atenção aos Povos Indígenas). Despite the progress, the lack of assurance of adequate infrastructure for the running of the indigenous schools, in addition to the lack of regulation of indigenous instructors which hinders the creation of new courses for the training of instructors in the state, constitute major impediments for the effectuation of an indigenous education in the state that fully respects what is determined by national policy.